Comparative Study of Wooded Angiospermic Diversity of the Two Protected Areas (Purna Wildlife Sanctuary and Jessore Wildlife Sanctuary) in Two Biogeographic Regions Of Gujarat, India - Yadav, Rajkumar S.; Suthar, Ashok; Kamboj, Ravi Dutt (Indian Forester, 2018)
The wooded angiospermic plants have rendered very important role in the ecological equilibrium and livelihood to the forest dwellers. Its diversity, composition and richness varies from place to place as per geographical settings. The object of this study was to determine the diversity and composition in the wooded angiospermic plant in two Protected Areas viz., Purna Wildlife Sanctuary (PWS) and Jessore Wildlife Sanctuary (JWS) of two different bio-geographical zones of Gujarat state. The qualitative and quantitative study has been completed through transect and quadrate methods. The results revealed that both Protected Areas have floristic heterogeneity in their jurisdiction and the qualitative examination of the both the sanctuaries indicated that a total of 136 species of trees and 32 species of shrubs exist in the PWS. However, the JWS showed a total of 84 species of trees and 27species of shrubs in their jurisdiction which is fewer than PWS. The quantitative analysis also showed that the density, frequency and abundance of wooded angiospermic plants are higher in the PWS than JWS. The biodiversity indices have shown that the species richness of trees in the PWS and JWS is good. However, the shrub composition and richness have shown decline in both of the sanctuaries. The similarity and dissimilarity indices have shown that the tree species are more diverse (63%) than shrub species (37%) in the both of the Protected Areas. Due to two different bio-geographical zones present in the study area, it has its own unique but distinct vegetation composition and diversity.